PERANCANGAN PROTOTYPE SISTEM PENGAMAN MENGGUNAKAN RFID YANG DIENSKRIPSI DAN TERMONITOR BERBASIS MICROCONTROLLER ARDUINO - Alfith Alfith (Ensiklopedia of Journal, 2022)
The door lock system still uses conventional locks, so it is less efficient for home security, apart from thieves. So that a more practical and efficient key is needed, from this problem the writer has an idea to produce a safe and practical RFID-based door security device by utilizing e-KTP as an RFID tag as security for the door of the house. The design of a security system prototype using RFID which is encrypted and monitored based on the Arduino microcontroller as a controller, the conventional key is easy to open the circuit. This study uses the research and development method that aims to produce and develop certain product. This method is applied to the research procedure into 9 stages, namely (1) starting, (2) potential and problems, (3) gathering information, (4) designing tools, (5) validating the design, (6) making tools, (7) testing, (8) data collection, and (9) data analysis. Based on the test result, it can be concluded that the simulation of the door safety device can operate properly, according to the design made. The RFID reader used has a frequency of 13.56MHz. Solenoid can unlock the door if the e-KTP ID matches the Arduino nano microcontroller memory, the solenoid will lock again within 10 second.Keywords: RFID, Frequency, Solenoid, Arduino Nano Microcontroller